Hadith #2181 - Sahih al-Bukhari - Ya'la bin 'Ata' يعلى بن عطاء العامري (Sahih al-Bukhari)
I fought in Jaish-al-Usra (Ghazwa of Tabuk) along with the Prophet (ﷺ) and in my opinion that was the best of my deeds. Then I had an employee, who quarrel led with someone and one of the them bit and cut the other’s finger and caused his own tooth to fall out. He then went to the Prophet (with a complaint) but the Prophet (ﷺ) canceled the suit and said to the complainant, “Did you expect him to let his finger in your mouth so that you might snap and cut it (as does a stallion camel)?”
Grade: Sahih

Hadith #4613 - Sahih al-Bukhari - Ya'la bin 'Ata' يعلى بن عطاء العامري (Sahih al-Bukhari)
I heard the Prophet (ﷺ) reciting when on the pulpit: ‘They will cry, “O Malik (Keeper of Hell) Let your Lord make an end of us.’ (43.77)
Grade: Sahih

Hadith #6637 - Sahih al-Bukhari - Ya'la bin 'Ata' يعلى بن عطاء العامري (Sahih al-Bukhari)
I went out in one of the Ghazwa and a man bit another man and as a result, an incisor tooth of the former was pulled out. The Prophet (ﷺ) cancelled the case.
Grade: Sahih

Hadith #591 - Sunan al-Nasa'i - Amr bin 'Absa al-Salmi; Ayoub al-Sakhtiyani أيوب السختياني; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Tlq يزيد بن طلق (Sunan al-Nasa'i)
“I prayed with the Prophet (ﷺ) in Al-Madinah, eight together and seven together. He delayed Zuhr and brought ‘Asr forward, and he delayed Maghrib and brought ‘Isha’ forward.”
Grade:

Hadith #858 - Sunan al-Nasa'i - Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir bin Yazid bin al-Aswad جابر بن يزيد بن الأسود; Ya'la bin 'Ata' يعلى بن عطاء العامري; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say: ‘Whoever does wudu’ properly, then walks to (attend) the prescribed prayer, and prays with the people or with the congregation or in the Masjid, Allah will forgive him his sins.”
Grade:

Hadith #1334 - Sunan al-Nasa'i - Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ya'la bin 'Ata' يعلى بن عطاء العامري; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“I watched the Messenger of Allah (ﷺ) when he prayed, and I noticed that his standing, his bowing, his standing up after bowing, his prostration, his sitting between the two prostrations and his sitting between the taslim and departing were almost the same in length.”
Grade:

Hadith #1666 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; ibn Umar; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
“I saw the Prophet (ﷺ) praying while sitting cross-legged.”
Grade:

Hadith #3987 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Muhammad bin Abi 'Adi محمد بن أبي عدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘I have been commanded to fight the people until they say La ilaha illallah. If they say it, then their blood and wealth are prohibited for me, except for a right that is due, and their reckoning will be with Allah.'”
Grade:

Hadith #3989 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Amr bin Hisham عمرو بن هشام; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Mkhld bin Yazid al-Quraishi مخلد بن يزيد القرشي الحراني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
“We were with the Messenger of Allah said: ‘Do not kill him, for I have been commanded to fight the people until they say La ilaha illallah, and if they say it, their blood and their wealth are safe from me, except for a right that is due, and their reckoning will be with Allah.'”
Grade:

Hadith #4182 - Sunan al-Nasa'i - Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ya'la bin 'Ata' يعلى بن عطاء العامري; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“We came in a delegation to the messenger of Allah, each of us with a question to ask him. I was the last of them to come in to the Messenger of Allah, and I said: ‘O Messenger of Allah, I have left people behind me, and they are saying that emigration (Hijrah) has ceased.’ He said: ‘Emigration will not cease so long as the disbelievers are being fought.”‘
Grade:

Hadith #4233 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
the Messenger of Allah forbade Fara’ and ‘Atirah.”
Grade:

Hadith #5509 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
“When the Prophet traveled, he would seek refuge with Allah from the hardships of travel, and the sorrows of return, from loss after plenty, from the supplication of the one who has been wronged, and from seeing some calamity befall.”
Grade:

Hadith #5510 - Sunan al-Nasa'i - Abu 'Alqama Mwla bina Hashim أبو علقمة مولى بني هاشم; Abu Hurairah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
“When the Messenger of Allah traveled and rode his mount, he gestured with his finger – and Shu’bah (one of the narrators) stretched out his finger – and said: ‘Allahumma, antas-sahibu fis-safari wal-khalifatu fil-ahli wal-mal. Allahumma, inni a’udhu bika min wa’tha’is-safari, wa kabatil-munqalabi (O Allah, You are our help when we are traveling and the One Who takes care of our families and wealth (in our absence). O Allah, I seek refuge in You from the hardships of travel and
Grade:

Hadith #5511 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Seek refuge with Allah from a bad neighbor in one’s permanent abode, for one’s neighbor in the desert will change.'”
Grade:

Hadith #5722 - Sunan al-Nasa'i - Abdullah bin Mubarak عبد الله بن المبارك; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan al-Nasa'i)
He disliked to sell raisins to one who would use them to make Nabidh.
Grade:

Hadith #2605 - Sunan Abi Dawud - Amarh bin Hdyd al-Bjly عمارة بن حديد البجلي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
It was rarely that the Messenger of Allah (ﷺ) set out on a journey on any day but on a Thursday.
Grade: Sahih

Hadith #4729 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Waki' bin al-Jarrah وكيع بن الجراح; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
When we are were sitting with the Messenger of Allah (May peace be upon him) he looked at the moon on the night when it was full, that is, fourteenth, and said : You will see your Lord as you see this (moon) and have no doubts about seeing him. If, therefore, you can keep from being prevented from prayer before the sun rises and before it sets, do so. He then recited :”Celebrate the praise of your Lord before the rising of the sun and before its setting”.
Grade: Sahih

Hadith #5018 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
A believer’s vision is the forty-sixth part of Prophecy.
Grade: Sahih

Hadith #5065 - Sunan Abi Dawud - Abu Hurairah; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
The Prophet (ﷺ) said: There are two qualities or characteristics which will not be returned by any Muslim without his entering Paradise. While they are easy, those who act upon them are few. One should say: “Glory be to Allah” ten times after every prayer, “Praise be to Allah” ten times and “Allah is Most Great” ten times. That is a hundred and fifty on the tongue, but one thousand and five hundred on the scale. When he goes to bed, he should say: “Allah is Most Great” thirty-f
Grade: Sahih

Hadith #5231 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
Ghalib said: When we were sitting at al-Hasan’s door, a man came along. He said: My father told me on the authority of my grandfather, saying: My father sent me to the Messenger of Allah (ﷺ) and said: Go to him and give him a greeting. So I went to him and said: My father sends you a greeting. He said: Upon you and upon your father be peace.
Grade: Hasan

Hadith #219 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Jabir bin Yazid bin al-Aswad جابر بن يزيد بن الأسود; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
“I attended Hajj with the Prophet. I prayed the Subh (Fajr) prayer with him in Masjid AI-Khaif.” He said: “When the Prophet finished, he turned (from the Qiblah) and saw two men at the back of the people who had not prayed with him. He said, ‘Bring them to me.’ So I brought then while they were shuddering with fear. He said: ‘What prevented you from praying with us?” They said: ‘O Messenger of Allah!’ We prayed at our camp.’ So he said: ‘Do not do that; when you pray in you
Grade:

Hadith #597 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu 'Ali al-Azdi أبو علي الأزدي; ibn Umar; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
the Prophet said: “The Salat during the night and the day is two and two.”
Grade:

Hadith #1383 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin al-'Aas; Muhammad bin Abi 'Adi محمد بن أبي عدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
from his father that the Prophet (ﷺ) set aside a land reserve for him in Hadramawt. (One of the narrators added): “And he sent Mu’awiyah with him to reserve it for him.”
Grade:

Hadith #1954 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin al-'Aas; Amr bin Abi Salmah عمرو بن أبي سلمة التنيسي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
“There is no gift that a father gives his son more virtuous than good manners.”
Grade:

Hadith #1955 - Jami' al-Tirmidhi - Abdullah bin 'Amr bin al-'Aas; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
“The Prophet would accept gifts and he would give something in return.”
Grade:

Hadith #2377 - Jami' al-Tirmidhi - Mahmud bin Ghaylan محمود بن غيلان العدوي مولاهم أبو أحمد; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Da'ud bin al-Jarud سليمان بن داود أبو داود الطيالسي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Jami' al-Tirmidhi)
“A man is upon the religion of his friend, so let one of you look at whom he befriends.”
Grade:

Hadith #2378 - Jami' al-Tirmidhi - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
“Three follow the deceased, two of them return, and one remains. He is followed by his family, his wealth, and his deeds. So his family and his wealth returns, and his deeds remain.”
Grade:

Hadith #3310 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Hammad bin Salama حماد بن سلمة; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
“We were with the Messenger of Allah when Surat Al-Jumuah was revealed, so he recited it until he reached: And other among them who have not yet joined them, A man said to him: ‘O Messenger of Allah! Who are these people who have not yet joined us?’ But he did not say anything to him.” He said: “Salman was among us.” He said: “So the Messenger of Allah placed his hand upon Salman and said: ‘By the One in whose Hand is my soul! If faith were on Pleiades then men among these peopl
Grade:

Hadith #185 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Salama حماد بن سلمة; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
The Messenger of Allah said: ‘Woe to the heels because of Hell-fire.'”
Grade:

Hadith #186 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Salama حماد بن سلمة; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“Aishah saw ‘Abdur-Rahman performing abluti0on, and she said: Perform ablution properly, for I heard the Messenger of Allah say: ‘Woe to the Achilles’ tendon because of Hell-fire.'”
Grade:

Hadith #187 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Salama حماد بن سلمة; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
The Prophet said: “Woe to the heels because of Hell-fire.”
Grade:

Hadith #296 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin 'Absa al-Salmi; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Tlq يزيد بن طلق (Sunan Ibn Majah)
“I saw the Messenger of Allah wiping over his leather socks and turban.”
Grade:

Hadith #1309 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin 'Absa al-Salmi; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Tlq يزيد بن طلق (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) cursed women who visit graves.”
Grade:

Hadith #1383 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Umar; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Waki' bin al-Jarrah وكيع بن الجراح; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Ibn Majah)
“He used to fast all of Sha’ban, until he joined it to Ramadan.”
Grade:

Hadith #1426 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin 'Absa al-Salmi; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ya'la bin 'Ata' يعلى بن عطاء العامري; Yazid bin Tlq يزيد بن طلق (Sunan Ibn Majah)
“Eat Suhur, for in Suhur there is a blessing.”
Grade:

Hadith #2321 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amarh bin Hdyd al-Bjly عمارة بن حديد البجلي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Ibn Majah)
“Do not cut off (the thief’s hand) except for something worth one quarter of a Dinar or more
Grade:

Hadith #3671 - Sunan Ibn Majah - Amr bin Rafa'i al-Advi. Client Of 'Umar عمرو بن رافع العدوي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Ibn Majah)
“The adulterer, at the time he is committing adultery, is not a believer; (the wine drinker) at the time he is drinking, is not a believer; the thief, at the time he is stealing, is not a believer; the plunderer, at the time he is plundering with the people looking on, is not a believer.”
Grade:

Hadith #3912 - Sunan Ibn Majah - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Ibn Majah)
“Whoever humbles himself one degree for the sake of Allah, Allah will raise him in status one degree, and whoever behaves arrogantly towards Allah one degree, Allah will lower him in status one degree, until He makes him among the lowest of the low.”
Grade: